Analisis Strategi Komunikasi Corporate Social Responcibility dan Pengorganisasian Informasi pada Multi-Stakeholder - Ghita Azmi Shafany; Choiria Anggraini (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to find out how Podomoro Park Bandung uses CSR communication strategies and organizing information for multi-stakeholders. This study used a qualitative approach with a case study approach, in which field observations and in-depth interview data collection techniques were used. The results of the study show that Podomoro Park Bandung has implemented a model of organizing CSR information and communication strategies from the bottom up. The Podomoro Park Bandung CSR communication strategy uses information organization to find related information that fits the needs of stakeholders. The conclusion of this research is that by using this information organizing strategy, Podomoro Park Bandung hopes to achieve bigger goals in its CSR program. Keywords: Information Organizing, Corporate Social Responsibility, Strategy.